Effects of Smoking on the Level of Lipase Enzyme and Lipid Profile in Blood Serum of Young Smokers (Medico Legal Update, 2020)
Cigarette smoking is a major risk factor for heart disease and peripheral vascular disorders. The cardiovasculardiseases among smokers can be predicted by the levels of lipid profile. The objective of the present studyis to analyse the effects of smoking on the lipid profile and lipase levels among Iraqi smokers as well as toidentify the morbidity risk among smokers and non-smokers. A cross-sectional study (n=50) was designedincluding smokers (n=40) and nonsmokers (n=10) as a control group.The lipid profile and lipase level testswere performed after overnight fasting.The lipid profile and lipase levels were found to be significantly(p?0.05) increased in the smoker group as compared to non-smoker group. Total cholesterol and triglyceride(TG) levels were found to be increased 194.24±37.04mg/dl and 173.87±44.96mg/dl in the smoker groupas compared to control (165.35±23.6mg/dl and 106.7±43.4mg/dl), respectively. Serum high-densitylipoprotein cholesterol (HDL) concentration was decreased to 46.30±7.1mg/dl as compared to control group64.15±8.8mg/dl.The smoker group showed significant increased in the serum LDL (103.16±21.43mg/dl)and VLDL (44.78±8.9mg/dl) levels as compared to control group (77.06±20.5md/dl and 24.14±8.8mg/dl,respectively). Similarly, the smoker group showed decreased in serum lipase level (28.35±78.3) as comparedto the control group (37.65±9.7). Smoking is associated with many risk factors of heart and vascular diseaseswhich can evaluated by the elevated levels of total cholesterol, TG, LDL and VLDL. However, preventivestrategies are needed to avoid the future cardiovascular diseases and in supporting the benefits of quittingsmoking.